Resolving the incompatibility of hydrodynamics calculations between popular BEM solvers (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This paper compares different Boundary ElementMethod (BEM) solvers used to calculate hydrodynamiceffects on floating bodies to reveal divergence intheir calculations due to different modeling conventions.These differences become evident when analyzing differentwave headings, multiple bodies, or non-axisymmetricfloating bodies, i.e., situations where the pose, orientation,and position of the body with respect to the global referenceframe and coordinate frame will influence the hydrodynamicscalculations. BEM-based solvers use the LinearPotential Flow Theory (LPFT) which is a common midfidelitymodeling approach for offshore floating structures.In this work we show that there is a lack of consensus inthe commonly used BEM solvers, viz., WAMIT, Capytaine,NEMOH, AQWA, HAMS, and OrcaWave. We demonstratethe differences in hydrodynamic coefficients calculatedby different BEM solvers by considering two triangularprisms. The available documentation for the BEM solversat the time of writing, along with communications withthe developers of these BEM solvers left some ambiguities.However, this work was able to reverse-engineer the causefor the differences in the results in a systematic manner.Furthermore, this work presents mathematical expressionsthat can convert hydrodynamic coefficients from each ofthe considered BEM solvers so as to enable verify of thehydrodynamic calculations across different BEM solvers.Finally, the findings were implemented in BEMRosetta(https://github.com/BEMRosetta/BEMRosetta) so that thegeneral community can easily convert or verify their hydrodynamiccalculations.